Hybridized Local and Charge-Transfer Excited-State Emitter for a Blue Organic Solid-State Laser - Jang, Ho Jin; Jeon, Gyudam; Patel, Khushbu; Lee, Hakjun; Kim, Taekyung; Lee, Jun Yeob; Ha, Na Young (ACS Applied Materials and Interfaces, 2023)
The use of triplet excitons harvesting and short exciton lifetime organic emitters is important to improve the exciton utilization in organic semiconductor laser diodes. In this study, a hybridized local and charge-transfer (HLCT)-type molecule, 11-(3-(10-(4-(1-phenyl-1H-phenanthro[9,10-d]imidazol-2-yl)phenyl)anthracen-9-yl)phenyl)-11H-benzofuro[3,2-b]carbazole (PhAnMBf), is used as an emitter for blue-emitting organic solid-state lasers (OSSLs). The short exciton lifetime and high photoluminescence quantum yield of the PhAnMBf emitter allowed the fabrication of an organic laser with an emission wavelength of 453 nm, a small full width at half-maximum of 1.2 nm, and a threshold of 105 nJ/pulse, corresponding to 44 μJ/cm2, on the distributed feedback substrate. The anthracene-based PhAnMBf material showed the potential of the HLCT emitter as an OSSL.
Keywords: Blue-emission; Charge-transfer excited state; Distributed feedback; Exciton lifetime; Hybridized local and charge transfer; Organic emitters; Organic semiconductor lasers; Organic solid-state lasers; Semiconductor laser diodes; Triplet excitons; blue emission; distributed feedback; hybridized local and charge transfer; optical pumping; organic solid-state laser